Accessibility to Education during the “Coup-Vid”: An Overview of Online Learning in Myanmar - Kato Yuka (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
While the concept of online classes is not new to the rest of the world, this became a common mode of learning in Myanmar only when the COVID-19 challenges became a reality in 2020 as physical classrooms could no longer be used. When the coup d’etat was staged in 2021, education was further halted since many schools and their students did not have the resources to teach and learn online in addition to the political instability. However, online learning has been trending on social media for those who do have access to these resources. This paper will investigate the ways in which young people engage in education facing the “coup–vid” (coup + COVID-19), the motivation behind such engagement, and insights how they are benefiting from digital tools for learning.